ANALISIS KARAKTERISTIK KEWIRAUSAHAAN DAN MODAL USAHA DALAM PENGEMBANGAN USAHA JAMBU METE UD MUBARAQ LOMBE DI KOTA KENDARI - Andriani, Mega (Business UHO: Jurnal Administrasi Bisnis, 2019)
Mega Andriani (C1A315088), 2019. Analysis of Characteristic of Kewirausahaan and Capital Employed of In Development of is Effort Jambu Mete UD Mubaraq Lombe [in] Town Kendari. Guided by Bpk Arifin Utha as counsellor I and Ms. Ninik Endang Purwati as counsellor II.This Research aim to to analyse the characteristic of kewirausahaan and capital employed in development of is effort jambu mete UD Mubaraq Lombe in Town Kendari. As for informan in this research as much 4 one who [is] consisted of by the owner of[is effort, manager and two people of warehouse custodian. Research type used in this research is descriptive research type, by using approach qualitative. Data collecting use the: observation, interview, and documentation.Result of this research indicate that the Characteristic kewirausahaan of pursuant to dimension of self confidence which have base to confidence, orienting duty and result, dare to risk, and orient the future with the the dimension implementation hence will develop the effort, at one blow capital exploiting by xself can improve the development of is effort jambu mete UD Mubaraq Lombe in Town Kendari .